(untitled) (Ibrahim Cardiac Medical Journal, 2016)
Background and Objectives: For diagnosis of nosocomial pneumonia in patients on ventilator, invasive procedure like bronchoscopy for microscopy and quantitative cultures of lower respiratory tract samples is useful but not always possible for potential risk of the procedure and the associated cost. The non-bronchoscopic sampling of the lower airways and quantitative cultures of tracheal aspirate may offer simple and readily available alternative to bronchoscopy with promising results. This study was done to evaluate the efficacy of blind tracheal aspirate in the microbiological diagnosis of nosocomial pneumonia occurring in intubated patients on mechanical ventilator. Materials & Methods: This cross-sectional study was carried out in the Intensive Care Unit in the Department of Critical Care Medicine, BIRDEM Hospital, Dhaka over a period 16 months starting from January 2010 to April 2011. A total of 54 clinically diagnosed cases of nosocomial (hospital acquired) pneumonia who were on ventilator were consecutively included in the study based on predefined enrolment criteria. All the 54 cases were subjected to blind endotracheal aspirate (BTA) followed by bronchoalveolar lavage (BAL) for quantitative cultures of specimens and isolation of causative microorganisms from them. Result: The present study showed that the mean age of the patients was 61 years (range: 24-86 years). Males were predominant in the series with male to female ratio being 7:3. Majority of the patients was haemodynamically stable as indicated by mean blood pressures, heart rate, temperature and respiratory rate. Most (83.3%) of the cases showed significant growth of microbes on culture of blind tracheal aspirates at cut-off value of 105 colony forming unit/ml (cfu/ml), while 87% of the cases exhibited positive growth on culture of bronchoalveolar lavage at cut-off value of 104 cfu/ml. Acinetobacter baumannii was the predominant organism isolated from BTA (73.3%) followed by Pseudomonas aeruginosa (33.3%). An almost similar pattern of growth was evident in BAL with more than 70% being Acinetobacter baumannii and about 30% Pseudomonas aeruginosa. C. albicans. Kiebsiella sp., E. coli, and Flavobacter were less commonly observed in either group. The Kappa test revealed a good agreement (70.7%) between the two procedures suggesting that the two diagnostic modalities are almost comparable in diagnosing pneumonia in patients admitted in ICU (p < 0.001). Conclusion: The study concluded that the accuracy of blind tracheal aspirate and bronchalveolar lavage in the diagnosis of nosocomial pneumonia was fairly comparable. The strength of agreement between the two diagnostic modalities is also good encouraging its use instead of more invasive procedures like BAL in the diagnosis of hospital-acquired pneumonia who are on mechanical ventilator. Ibrahim Cardiac Med J 2014; 4(2): 49-55